Nonstationary First Threshold Crossing Reliability for Linear System Excited by Modulated Gaussian Process - Rita Greco; Giuseppe Carlo Marano; Alessandra Fiore; Ivo Vanzi (Shock and Vibration)
A widely used approach for the first crossing reliability evaluation of structures subject to nonstationary Gaussian random input is represented by the direct extension to the nonstationary case of the solution based on the qualified envelope, originally proposed for stationary cases. The most convenient way to approach this evaluation relies on working in the time domain, where a common assumption used is to adopt the modulation of stationary envelope process instead of the envelope of modulated stationary one, by utilizing the so-called “preenvelope” process. The described assumption is demonstrated in this work, also showing that such assumption can induce some errors in the envelope mean crossing rate.